Ground‐based ELF/VLF chorus observations at subauroral latitudes—VLF‐CHAIN Campaign. Issue 9 (22nd September 2014) - Shiokawa, Kazuo; Yokoyama, Yu; Ieda, Akimasa; Miyoshi, Yoshizumi; Nomura, Reiko; Lee, Sungeun; Sunagawa, Naoki; Miyashita, Yukinaga; Ozaki, Mitsunori; Ishizaka, Kazumasa; Yagitani, Satoshi; Kataoka, Ryuho; et al.
Abstract We report observations of very low frequency (VLF) and extremely low frequency (ELF) chorus waves taken during the ELF/VLF Campaign observation with High‐resolution Aurora Imaging Network (VLF‐CHAIN) of 17–25 February 2012 at subauroral latitudes at Athabasca (L=4.3), Canada. ELF/VLF waves were measured continuously with a sampling rate of 100 kHz to monitor daily variations in ELF/VLF emissions and derive their detailed structures. We found quasiperiodic (QP) emissions whose repetition period changes rapidly within a period of 1 h without corresponding magnetic pulsations. QP emissions showed positive correlation between amplitude and frequency sweep rate, similarly to rising‐tone elements. We found an event of nearly simultaneous enhancements of QP emissions and Pc1/electromagnetic ion cyclotron wave intensities, suggesting that the temperature anisotropy of electrons and ions developed simultaneously at the equatorial plane of the magnetosphere. We also found QP emissions whose intensity suddenly increased in association with storm sudden commencement without changing their frequency. Falling‐tone ELF/VLF emissions were observed with their rate of frequency change varying from 0.7 to 0.05 kHz/s over 10 min. Bursty‐patch emissions in the lower and upper frequency bands are often observed during magnetically disturbed periods. Clear systematic correlation between these various ELF/VLF emissions and cosmic noise absorption was not obtained throughout the campaign period. These observations indicate several previously unknown features of ELF/VLF emissions in subauroral latitudes and demonstrate the importance of continuous measurements for monitoring temporal variations in these emissions.